The Correlation between Cognitive Emotion Regulation and Spiritual Intelligence with Quality of Life among Emergency Department Nurses - S Barghandan; J Khalatbari (Iran University of Medical Sciences, 2017)
Abstract Background & Aim: The nurses in the emergency department undergo a lot of stress that can influence their quality of life. The aim of the present study was to investigate the relationship between cognitive emotion regulation and spiritual intelligence with quality of life in the emergency department nurses. Material & Methods: This study was a descriptive- correlational research including 100 nurses working in the private hospitals of Rasht in 2013. We selected participants by using cluster sampling method. The instruments were the Cognitive emotion regulation, King spiritual intelligence and Quality of life questionnaires. For statistical analysis of data the SPSS software (version 16) and the descriptive statistics, linear regression and multiple stepwise regression was used. Results: The results showed a significant positive correlation between the cognitive emotion regulation compatible strategies and spiritual intelligence with quality of life of nurses in emergency department (P≤ 0.01) and there was a significant negative correlation between cognitive emotion regulation incompatible strategies and Spiritual intelligence with quality of life of the emergency department nurses (P≤ 0.05). Conclusion: According to correlation between cognitive regulations of emotional and spiritual relationship with quality of life in the emergency department nurses, then it is necessary to consider training for increasing their quality of life.